Development Of A Malaysian Ocean Wave Database And Models For Engineering Purposes - Yaakob, Omar (Universiti Teknologi Malaysia, 2006)
Correct wave data is a very important input to predict the performances of the marine vehicles and structures at preliminary design stages particularly regarding safety, effectiveness and comfort of passengers and crews. Presently, available wave data in Malaysian seas are based on visual observations from ships, oil platforms and limited wave buoys whose accuracy, reliability and comprehensiveness are often questioned. This study presents an effort to derive a more reliable and comprehensive wave database for Malaysian sea areas using satellite altimetry. Significant wave height, wind speed and sigma0 data is extracted from oceanographic satellite TOPEX/Poseidon for selected area. Results are presented in the form of probability distribution functions and compared to data from Global Wave Statistics (GWS), Malaysian Meteorological Service (MMS), Petronas Research Scientific Services (PRSS) and United State National Data Buoy Center (NDBC). This project has shown that the data provided by TOPEX/Poseidon satellite can be used to derive wave periods and the results indicate that the Hwang Method was the best approach to derive wave period for Malaysian ocean data.